miR-125b affects mitochondrial biogenesis and impairs brite adipocyte formation and function - Giroud M; Pisani DF; Karbiener M; Barquissau V; Ghandour RA; Tews D; Fischer-Posovszky P; Chambard JC; Knippschild U; Niemi T; Taittonen M; Nuutila P; et al. (ELSEVIER SCIENCE BV, 2022)
Objective: In rodents and humans, besides brown adipose tissue (BAT), islands of thermogenic adipocytes, termed "brite" (brown-in-white) or beige adipocytes, emerge within white adipose tissue (WAT) after cold exposure or beta 3-adrenoceptor stimulation, which may protect from obesity and associated diseases. microRNAs are novel modulators of adipose tissue development and function. The purpose of this work was to characterize the role of microRNAs in the control of brite adipocyte formation.Methods/Results: Using human multipotent adipose derived stem cells, we identified miR-125b-5p as downregulated upon brite adipocyte formation. In humans and rodents, miR-125b-5p expression was lower in BAT than in WAT. In vitro, overexpression and knockdown of miR-125b-5p decreased and increased mitochondrial biogenesis, respectively. In vivo, miR-125b-5p levels were downregulated in subcutaneous WAT and interscapular BAT upon beta 3-adrenergic receptor stimulation. Injections of an miR-125b-5p mimic and LNA inhibitor directly into WAT inhibited and increased beta 3-adrenoceptor-mediated induction of UCP1, respectively, and mitochondrial brite adipocyte marker expression and mitochondriogenesis.Conclusion: Collectively, our results demonstrate that miR-125b-5p plays an important role in the repression of brite adipocyte function by modulating oxygen consumption and mitochondrial gene expression. (C) 2016 The Author(s). Published by Elsevier GmbH. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).